A dinuclear ruthenium(ii) phototherapeutic that targets duplex and quadruplex DNA. Issue 12 (26th February 2019) - Archer, Stuart A.; Raza, Ahtasham; Dröge, Fabian; Robertson, Craig; Auty, Alexander J.; Chekulaev, Dimitri; Weinstein, Julia A.; Keane, Theo; Meijer, Anthony J. H. M.; Haycock, John W.; MacNeil, Sheila; Thomas, James A.
Abstract : A previously reported dinuclear DNA imaging probe has been converted into a phototherapeutic through the incorporation of Ru II (TAP)2 fragments (TAP = 1, 4, 5, 8-3 tetraazaphenanthrene). Abstract : With the aim of developing a sensitizer for photodynamic therapy, a previously reported luminescent dinuclear complex that functions as a DNA probe in live cells was modified to produce a new iso-structural derivative containing Ru II (TAP)2 fragments (TAP = 1, 4, 5, 8-tetraazaphenanthrene). The structure of the new complex has been confirmed by a variety of techniques including single crystal X-ray analysis. Unlike its parent, the new complex displays Ru → L-based 3 MLCT emission in both MeCN and water. Results from electrochemical studies and emission quenching experiments involving guanosine monophosphate are consistent with an excited state located on a TAP moiety. This hypothesis is further supported by detailed DFT calculations, which take into account solvent effects on excited state dynamics. Cell-free steady-state and time-resolved optical studies on the interaction of the new complex with duplex and quadruplex DNA show that the complex binds with high affinity to both structures and indicate that its photoexcited state is also quenched by DNA, a process that is accompanied by the generation of the guanine radical cation sites as photo-oxidization products. Like the parent complex, this new compound is taken up by live cells where it primarily localizes within the nucleus and displays low cytotoxicity in the absence of light. However, in complete contrast to [{Ru II (phen)2 }2 (tpphz)] 4+, the new complex is therapeutically activated by light to become highly phototoxic toward malignant human melanoma cell lines showing that it is a promising lead for the treatment of this recalcitrant cancer.